Volcanoes of Zealandia and the Southwest Pacific. Issue 4 (1st October 2020) - Mortimer, Nick; Scott, James M.
ABSTRACT: New Zealand and the southwest Pacific region have a well-preserved geological record of Late Cretaceous to Holocene volcanism. Volcanoes and volcanic fields formed in six main tectonic settings: (1) oceanic crust; (2) large igneous provinces; (3) subduction-related volcanic chains; (4) intraplate related to Late Cretaceous rifting of Zealandia from Gondwana; (5) intraplate in Cenozoic age progressive chains that define so-called hotspot tracks; and (6) intraplate with a scattered, Cenozoic, non-age progressive, non-rift-related distribution. At least 500 volcanic fields, stratovolcanoes and seamounts, active within the last 105 million years, can be identified within the c. 5 million km 2 area of Zealandia continental crust. Volcanic rocks from onland New Zealand are the best-studied and dated but represent material from less than a fifth of Zealandia's volcanoes and volcanic fields.